Impact of Urban Redevelopment on Low-Income Residential Segregation in South Korea’s Metropolitan Cities, 2011–2020 - Chaeyeon Lee; Donghyun Kim (Land)
Residential segregation, which has been centered on race and ethnicity, has recently expanded to include income and social class as social inequality has increased. In particular, South Korea is one of the countries where social inequality is increasing as a result of economic growth. Existing studies have considered a relationship between redevelopment and residential segregation with respect to income, but there is a lack of factual evidence incorporating analysis in terms of spatial units. We analyzed patterns of low-income residential segregation (LiRS) in South Korea from the macro and micro perspectives to determine the net effect of redevelopment on this phenomenon. By classifying recipients of the National Basic Livelihood Security System (NBLSS) as low-income people, we measured LiRS using the dissimilarity index, the isolation index, the location quotient, and local Moran’s I (LISA) in seven metropolitan cities in South Korea between 2011 and 2020. We explored the net effect of redevelopment on LiRS using propensity score matching (PSM), and we estimated that redevelopment would reduce LiRS by 0.0289. The findings reveal that low-income residential segregation declined from 2011 to 2020. PSM analysis indicates that redevelopment mitigates LiRS. This study provides insights into the need to consult with those responsible for low-income housing policies to ensure the positive impact of redevelopment on LiRS.